SPAWNING CONCENTRATIONS OF THE SARDINE, SARDINELLA GIBBOSA (BLEEKER), OFF THE NORTH ANDHRA COAST IN MARCH - APRIL 1969 - Sekharan, K V; Muthu, M S; Rao, G Sudha; Rao, B Narayana (Indian Journal of Fisheries, 2011)
Adult Sardinella gibbosa in pre-spawning and spawning stages were observed in March 1969 in Waltair - Kakinada region from catches made 15-20 km from shore. Plankton collections made during this period off Kakinada contained eggs which have been assigned to S. gibbosa based on circumstantial evidence and resemblances. Most of the stomachs of 5. ^/’66oM examined during the period were either empty or contained very little food. These indicate that there was extensive spawning of the species off the North Andhra coast in March-April 1969.